Theoretical Insights into the Activation and Conversion of Electrochemical CO2 Reduction on 3d Transition Metal‐Doped Cu(111) Stepped Structures - Lihong Yin; Jinxian Feng; Weng Fai Ip; Guangfu Luo; Hui Pan (ChemElectroChem, 2025)
The activation of CO2 is essential for efficient electrochemical conversion, yet its weak physisorption on pristine Cu surfaces severely hinders catalytic performance. To overcome this limitation, we designed Cu stepped structures to create highly reactive sites for enhanced CO2 adsorption and further doped the edges with 3d transition metals (V, Cr, Mn, Fe, Co, and Ni) to improve CO2 reduction. Density functional theory calculations reveal that these dopants significantly reduce the OCO angles and elongate the CO bonds, transforming CO2 from its original linear configuration into a bent geometry at the interface. Notably, dual‐V and dual‐Fe doping on Cu stepped surfaces demonstrates a strong interaction with CO2, leading to a high degree of activation. The computational results demonstrate that these modifications significantly enhance CO2 activation and favor methane generation. This study provides valuable insights into the design of advanced Cu‐based electrocatalysts for efficient and selective CO2 activation, offering a pathway toward sustainable CO2 utilization.